2019
DOI: 10.1557/adv.2019.251
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of 316L Stainless Steel Fabricated Using Selective Laser Melting

Abstract: ABSTRACTThe microstructure homogeneity and variability in mechanical properties of 316L stainless steel components fabricated using selective laser melting (SLM) have been investigated. The crack free, 99.9% dense samples were made starting from SS316L alloy powder, and the melt pool morphology was analysed using optical and scanning electron microscopy. Extremely fast cooling rates after laser melting/solidification process, accompanied by slow diffusion of alloying elements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The increments were 31.1%, 20.1% and 16.2%, respectively. Ipbal et al [ 33 ] found that the existence of the defects had a great negative effect on the microhardness of AM 316L. As discussed above, the effect of surface defects elimination due to laser polishing is an important factor for improving microhardness.…”
Section: Methodsmentioning
confidence: 99%
“…The increments were 31.1%, 20.1% and 16.2%, respectively. Ipbal et al [ 33 ] found that the existence of the defects had a great negative effect on the microhardness of AM 316L. As discussed above, the effect of surface defects elimination due to laser polishing is an important factor for improving microhardness.…”
Section: Methodsmentioning
confidence: 99%
“…To obtain high-performance final parts of SS316L manufactured by the LPBF process, current research interest in LPBF primarily focuses on optimizing process parameters, analyzing microstructures, characterizing mechanical properties, exploring post-processing techniques, and employing computational modeling and simulation. This collective research effort aims to advance our understanding and enhance the quality of SS316L parts produced via LPBF [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%